Antibacterial Test Of Telang Flower Extract (Clitorea Ternatea L.) Against Pseudomonas Aeruginosa - Luluk Aniqoh Meliana Putri; Chinthia Devientasaria (Strada Journal of Pharmacy, 2023)
The butterfly pea flower is a shrub that can grow and live for years (perennial), can reach a height of 5 meters, has fine hair, and is woody at the base, the flower color is bright blue with a yellowish white color in the middle. Butterfly pea flower (Clitoria ternatea L.) is a plant that has long been used in medicine and has been proven to contain alkaloid and flavonoid secondary metabolite compounds which have antibacterial potential. Antibacterials are substances that can interfere with the growth or even kill bacteria by interfering with the metabolism of harmful microbes. The aim of this research was to determine the inhibitory power of telang flower simplicia extract (Clitoria ternatea L.) on the growth of Pseudomonas aeruginosa bacteria. This research aims to test the activity of butterfly pea flowers, namely by maceration using 70% ethanol solvent. For antibacterial testing using the disk diffusion method. Extracts are made in various concentrations of 10%, 20%, 30%. The positive control used was Chloramphenicol. The results of this research were that the average zone of inhibition of butterfly pea flower extract against Pseudomonas aeruginosa bacteria was 1.48 mm at 10% concentration, 2.41 mm at 20% concentration, and 5.70 mm at 30% concentration. These results show that butterfly pea flower extract has antibacterial activity against Pseudomonas aeruginosa bacteria, although the resulting inhibitory power is not strong. At a concentration of 30% butterfly pea flower extract, it has the greatest inhibitory effect on the growth of Pseudomonas aeruginosa bacteria than concentrations of 10% and 20%.